DETERMINAN KINERJA PENGELOLAAN KEUANGAN DESA - Nasution, Ade Nur Rabbiah; Amalia, Dewi (Universitas Ahmad Dahlan, 2021)
This study aims to examine the factors that determinants of financial management performance in village government. Village financial management is all activities that include planning, implementation, administration, reporting and financial accountability of the village. The Village financial management is carried out based on the principles of governance: transparent, accountable and participatory so that good governance can be implemented in the village government administration system. The object of this research is Panggungharjo Village, Sewon District at Bantul Regency. The variables tested were the capacity of village officials, financial reporting compliance, and quality of supervision of the BPD. The method used in this research is the type of quantitative data which is strengthened by interviews and the samples are the village head, treasurer and BPD in Panggungharjo Village. Data collection in this study was conducted through a survey using a questionnaire technique to 39 respondents and structured interviews with the treasurer and BPD. The results of this study are the capacity of village officials, financial reporting compliance, and the quality of BPD supervision that affect the performance of financial management.Â Â